Treating Trauma in the Fishbowl of University & College Counseling Centers. Issue 3 (3rd July 2021) - Rosenbaum, Philip J.; Webb, Richard E.
ABSTRACT: The treatment of college students who have experienced trauma in their lives is commonplace in University and College Counseling Centers. Despite this, there is almost no literature on navigating the challenges of treating trauma in this context. Accordingly, in this paper, we discuss the importance for college counselors to consider the "fishbowl effect" when working with traumatized students. This refers to the ways that college students often share their concerns with a wide range of people, who in turn offer good-hearted advice. While this can be very useful as we discuss, it can also pose unique challenges for the treatment of trauma as these people do not often have an understanding of dissociation and enactment. We introduce these ideas and then use case examples throughout the paper to demonstrate their relevance to college counseling. Finally, we offer some thoughts on treating trauma within the fishbowl of higher education.